Flood Vulnerability Mapping of the Kosi River Basin using a Multi-Criteria Decision-Making Approach - Kumar, Akshay; Jha, Ramakar (Engineering, Technology & Applied Science Research, 2024)
The research presented in this study introduces a novel methodology for delineating flood-prone regions within the Kosi River Basin, utilizing a multi-criteria decision-making approach. This method integrates multi-criteria analysis, Geographical Information Systems (GIS), and Remote Sensing (RS). The specific process involves the creation of flood susceptibility maps based on five crucial factors: rainfall, land use/cover, slope, drainage density, and distance from the river. Expert judgments were incorporated and translated into weighted values to ascertain the relative significance of each factor in determining flood susceptibility. Weight calculations were performed using the Fuzzy Analytic Hierarchy Process (FAHP). The findings of this study indicate that across all 10 districts in the region, a varying degree of land area is classified as high-risk, with Madhubani displaying the highest percentage of land area categorized as of very high-risk. Key challenges include data accuracy and model generalization, with potential applications in other flood-prone areas. This approach not only improves the precision of flood susceptibility mapping, but also offers valuable insights for disaster management and planning in areas with limited data availability.